2012
DOI: 10.1371/journal.pone.0033820
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of Immunomodulation in Bivalves under Seawater Acidification and Increased Temperature

Abstract: Water acidification, temperature increases and changes in seawater salinity are predicted to occur in the near future. In such a global climate change (GCC) scenario, there is growing concern for the health status of both wild and farmed organisms. Bivalve molluscs, an important component of coastal marine ecosystems, are at risk. At the immunological level, the ability of an organism to maintain its immunosurveillance unaltered under adverse environmental conditions may enhance its survival capability. To our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(78 citation statements)
references
References 46 publications
4
73
0
1
Order By: Relevance
“…In showing immune system maintenance to be compromised by exposure to a reduced seawater pH of 6.50, this study would appear to support previous research on the impact of elevated seawater pCO 2 on the invertebrate immune response (Bibby et al, 2008;Matozzo et al, 2012). Bibby et al (2008) found that a 32 day exposure to OA reduced the ability of impacted mussels to increase phagocytic activity when compared to controls, suggesting that an increased haemolymph calcium concentration interfered with cellular signalling pathways, and thus immunocompetence.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In showing immune system maintenance to be compromised by exposure to a reduced seawater pH of 6.50, this study would appear to support previous research on the impact of elevated seawater pCO 2 on the invertebrate immune response (Bibby et al, 2008;Matozzo et al, 2012). Bibby et al (2008) found that a 32 day exposure to OA reduced the ability of impacted mussels to increase phagocytic activity when compared to controls, suggesting that an increased haemolymph calcium concentration interfered with cellular signalling pathways, and thus immunocompetence.…”
Section: Discussionsupporting
confidence: 85%
“…Hernroth et al (2011) also demonstrated a suppression of phagocytic activity, as well as a reduction in coelomocyte counts and an inhibition of p38 MAPkinase activity, in Asterias rubens exposed to pH 7.7. Similarly Matozzo et al (2012) demonstrated a reduction in host defence in mussels exposed to reduced seawater pH, with the lysozyme-like activity of cell free haemolymph reduced in Mytilus galloprovincialis exposed to pH 7.7 and 7.4 for 7 days.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Recently, it has been found that OA stress has the potential to promote pathogen development and survival, disease transmission and host susceptibility [33]. However, only few studies have investigated the immune responses of mollusks under OA stress so far [18,19,34].…”
Section: Discussionmentioning
confidence: 99%